Determination of Peripheral Artery Disease using Ankle-Brachial Index - Bakshi, Dr. Vasudha (Asian Journal of Pharmaceutics (AJP), 2019)
Aim: The main aim of this study is to determine peripheral artery disease (PAD) using ankle-brachial index (ABI) who is having the risk factors for developing PAD and also determine additional risk factors which are responsible for vascular risk leading to PAD in future and to assess the patients who are at high risk for developing complications such as stroke and coronary artery disease (CAD). Materials and Methods: A total number of 500 patients who met the study criteria were included in the study. The required data were collected by measuring ankle, brachial pressures for the patients and some data related to the patients were collected through patient’s case sheets and medical records. The collected data were analyzed statistically. Results and Discussion: It was observed that smoking is the major contributing risk factor for PAD. Diabetes is the second most contributing risk factor for PAD, followed by CAD, obesity, hypertension, dyslipidemia, and alcohol. The risk for PAD was observed to be more in males compared to females. PAD patients have remained asymptomatic even at severe risk. Moreover, the majority of the patients are at moderate risk for PAD. The patients with age group of 51–60 years were at a higher risk for PAD and testing the people with ABI of age above 50 years having PAD risk factors might be beneficial. Conclusion: Finally, the use of ABI as a screening test in all primary health-care settings could be useful to detect the risk for PAD at an early stage and can prevent further complications.